Differences in relaxation and imagery among NCAA Division I sport types - Warfield, E.; Esposito, P.; Braun-Trocchio, R. (Sports, 2023)
Athletes use psychological skills such as imagery and relaxation to decrease stress, cope with competitive anxiety, and achieve an optimal state of arousal. There is conflicting literature on how team and individual sport athletes use these skills, with some saying that individual sport athletes have better capabilities and others saying team sport athletes use imagery more frequently. The current study analyzed sport type differences in the use of relaxation and performance imagery among NCAA Division I (DI) athletes. This study included 117 NCAA DI athletes, including team sport (n = 72) and individual sport (n = 45). Participants completed a modified version of The Deliberate Relaxation for Sport Survey through Qualtrics. Results indicated there is a statistically significant difference in the type of relaxation technique used based on the individual`s sport type. Team sport athletes used muscle relaxation (p = 0.034), eastern relaxation (p = 0.014), and stretching (p = 0.020) more frequently than individual sport athletes. Additionally, individual sport athletes used performance imagery more often for mental focus than team sport athletes (p = 0.012). There were no differences between sport types in the level of deliberate practice of relaxation and performance imagery. Athletes used a variety of methods to learn both imagery and relaxation skills and have been using these for an average of four years. The majority of participants (n = 67) did not work with a sport psychology professional, but their school has one. This study supports the use of individualized intervention programs to help athletes use relaxation and imagery in the most effective ways for their performances.